Histomorphological and immunohistochemical characterization of 172 cutaneous round cell tumours in dogs - Marina Rios Araújo; Ingred Sales Preis; Gleidice Eunice Lavalle; Geovanni Dantas Cassali; Roselene Ecco (Pesquisa Veterinária Brasileira, 2012)
This paper describes the use of a panel of antibodies (CD117, CD3, CD79a, CD45, cytokeratin, vimentin and E-cadherin) on formalin-fixed, paraffin-embedded sections of canine cutaneous round cell tumours. Neoplastic tumours were diagnosed by histology and histochemical stains and included 107 mast cell tumours, 31 cutaneous histiocytomas, two localized histiocytic sarcomas, 21 cutaneous lymphomas, three plasma cell tumours, one transmissible venereal tumour and seven unclassified round cell tumours. The histologic diagnosis was modified in 39.5% of the total 172 neoplasms. The staining for CD45 and Ecadherin were variable, and therefore, the final diagnoses of cutaneous histiocytoma and localized histiocytic sarcoma were made based on histology in association with negative results for CD3, CD79a, CD117 and cytokeratin. The cellular origin of unclassified round cell tumours was defined in all cases. Cutaneous B-cell lymphoma and plasma cell tumours were CD79a-positive and could be distinguished from each other by the morphological characteristics. Mast cell tumours and T cell lymphoma were CD117 and CD3 positive, respectively. The positive staining for vimentin and the negative staining for CD3, CD79a, CD117 and cytokeratin favoured the diagnosis of transmissible venereal tumours. Thus, the final diagnosis of cutaneous round cell tumours should be based on the interpretation of immunohistochemical results together with the cellular morphology observed by histology. Therefore, more studies to optimize the specific markers in formalin-fixed, paraffinembedded tissues (especially for histiocytes) are required for definitive diagnosis of round cell tumours in dogs.